Pengaruh Kemudahan Pengguna dan Cashback terhadap Minat Beli Ulang Mahasiswa di Marketplace Lazada - Bayu Teta; Selvina Mariana Sitinjak; Jesica Theresia Purba2; Tiurlan Br manullang (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the effect of ease of use and cashback on students' repurchase intention on the Lazada marketplace. The research employs a quantitative approach with a survey method. The sample was obtained using accidental sampling, involving 55 active student users of Lazada. The instrument used a closed-ended questionnaire with a Likert scale, and both validity and reliability were tested. Data were analyzed using multiple linear regression. The results show that ease of use and cashback both have a significant partial and simultaneous effect on repurchase intention.